Analyses of a leaking styrene-acrylonitrile water-filter housing. (November 2015) - Zorc, Borut; Nagode, Aleš
Abstract: Fatigue cracks were found in water-filter housings made of styrene-acrylonitrile. These cracks initiated on the external surface, along the sharp corner between the wall of the housing and the vertical external ribs or at a pre-existing crack in the base of the water-filter housing. The reason for the crack was the high stress concentration due to an inappropriate design or the poor quality of the filter housing in combination with water-pressure impacts during the operation of an electromagnetic water valve and taps. Highlights: Fatigue cracks exist in a water-filter housing made of styrene-acrylonitrile. Quality of the styrene-acrylonitrile is good. Cracks initiated due to water-pressure impacts in areas of high stress concentration. Failure is due to improper design or a pre-existing crack in the base of the filter housing.